The Results of Hearing Screening at the Children ith Down Syndrome Andijan Region f Uzbekistan (Global Journal of Medical Research, 2022)
This article presents the primary results of targeted hearing screening among children with Down syndrome as one of the most common pathologies at risk of developing various forms of hearing loss As a result of the screening according to the data of delayed otoacoustic emission and otoacoustic emission distortion product out of the total number of children in 41 5 of cases objective tests showed the presence of auditory dysfunction i e the answer is refer Thus we found it expedient to carry out hearing screening in children with Down syndrome in order to prevent hearing loss and secondary forms of delayed psychoverbal development associated with it
Keywords: down syndrome; auditory screening; hearing loss; children with down syndrome; objective methods of audiometry